The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2012
DOI: 10.1373/clinchem.2012.192054
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Studies of Cardiac Troponin I in a Large Cohort of Healthy Children

Abstract: BACKGROUND:There is little information available on cardiac troponin concentrations in healthy young children.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0

Year Published

2013
2013
2019
2019

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(21 citation statements)
references
References 27 publications
2
19
0
Order By: Relevance
“…Apple and Collinson found that the short-term CV i was 15% (20 ), whereas Goldberg et al found that the shortterm CV i was 24% but the longer-term CV i (over 9 days) was 80% (21 ). A study looking at biological variation over several years in 453 healthy children found that the median CV i was 33% (13 ). Other than the study from Goldberg et al, these results are remarkably consistent in establishing that cTnI is an analyte with a small index of individuality.…”
Section: Discussionmentioning
confidence: 76%
“…Apple and Collinson found that the short-term CV i was 15% (20 ), whereas Goldberg et al found that the shortterm CV i was 24% but the longer-term CV i (over 9 days) was 80% (21 ). A study looking at biological variation over several years in 453 healthy children found that the median CV i was 33% (13 ). Other than the study from Goldberg et al, these results are remarkably consistent in establishing that cTnI is an analyte with a small index of individuality.…”
Section: Discussionmentioning
confidence: 76%
“…No studies found significant gender-related differences in cTnI values of pediatric age subjects (Table 2 and Figure 2) [15,33,34,50]. On the other hand, adult males usually present cTnI values that are, on average, twofold higher than those in women; in this age group, the calculated 99th URL values are strongly gender-dependent [14,29,49].…”
Section: Gendermentioning
confidence: 95%
“…concentration values higher than the LoD value of 1.3 ng/L) were clearly evidenced in more than 85% of a population of apparently healthy children (ages ranging from birth to adulthood) when a highly sensitive method was used for troponin measurement [15,33,34]. cTnI levels, at their highest in the first few weeks of life, tended to gradually decrease up to adulthood [15] (Table 2 and Figure 2).…”
Section: Agementioning
confidence: 98%
See 1 more Smart Citation
“…In recent years, technical improvements have led to the development of highsensitivity assays that are capable of measuring low concentrations of cardiac troponin with high precision. With such assays, we are now able to measure cardiac troponin in the serum of healthy individuals, including children, who have no evidence of cardiovascular disease (2)(3)(4). The advent of high-sensitivity assays has uncovered sexspecific differences in circulating cardiac troponin concentrations that were formerly unrecognized because previous assays could not measure cardiac troponin with sufficient precision at or below the 99th percentile.…”
Section: © 2016 American Association For Clinical Chemistrymentioning
confidence: 99%